2021
DOI: 10.1002/ddr.21907
|View full text |Cite
|
Sign up to set email alerts
|

Road‐map of pre‐clinical treatment for Visceral Leishmaniasis

Abstract: Visceral leishmaniasis (VL) or Kala‐azar, is the most lethal form of leishmaniasis, is still prevalent in many countries where it is endemic. It is a threat to human life caused by protozoan parasite Leishmania donovani. The severity of the disease is further increased as the treated individuals might have a chance of developing Post Kala‐azar Dermal Leishmaniasis (PKDL) in the long run. Moreover, several countries have reported high number of HIV‐VL co‐infected patients. Therefore, there is a dire need for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Pentavalent antimonials, such as SSG, are parenteral drugs that are given in doses of 20 mg/kg for 28–30 days when used as monotherapy; their mechanism of action is still poorly understood [ 61 ]. Despite the need for prolonged parenteral treatment and the risk of adverse affects, including cardiotoxicity (ventricular tachycardia, prolonged QTc interval, ventricular fibrillation, torsades de pointe), pancreatitis, pancytopenia, and nephrotoxicity, since their discovery in 1923, these drugs have been used for decades for the treatment of VL in the vast majority of endemic regions [ 7 , 62 , 63 ]. This probably happened because of the affordability and the time-tested effectiveness of this drug [ 64 ].…”
Section: Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Pentavalent antimonials, such as SSG, are parenteral drugs that are given in doses of 20 mg/kg for 28–30 days when used as monotherapy; their mechanism of action is still poorly understood [ 61 ]. Despite the need for prolonged parenteral treatment and the risk of adverse affects, including cardiotoxicity (ventricular tachycardia, prolonged QTc interval, ventricular fibrillation, torsades de pointe), pancreatitis, pancytopenia, and nephrotoxicity, since their discovery in 1923, these drugs have been used for decades for the treatment of VL in the vast majority of endemic regions [ 7 , 62 , 63 ]. This probably happened because of the affordability and the time-tested effectiveness of this drug [ 64 ].…”
Section: Therapymentioning
confidence: 99%
“…PM, an aminoglycoside antibiotic which blocks protein synthesis, was shown to be a cheap and effective parenteral drug easily administered intramuscularly with a dosage of 15 mg/kg/day, but it requires a 21-days course. Moreover, it is potentially nephrotoxic and ototoxic [ 51 , 63 ].…”
Section: Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the design of antileishmanial compounds have identified some novel pathways and protein targets necessary for the parasite’s survival [ 17 , 18 ]. Some of these targets have been validated [ 19 , 20 ], while investigation on others is still ongoing. Ergosterol biosynthesis is involved in various biological functions including plasma membrane formation, membrane fluidity, distribution of membrane proteins, and control of the cell cycle [ 21 ].…”
Section: Introductionmentioning
confidence: 99%